Identifikasi Kajian-Kajian Berkaitan Intervensi Preventif Bagi Pedofilia Berdasarkan Systematic Literature Review: (Identification of Studies Related to the Preventive Intervention of Pedophile Based on Systematic Literature Review) - Ahmad, Khadher; Zainal Abidin, Mohd Syukri; Abdullah, Mustaffa; Md Zin@Zakaria, Siti Rosmani; Md Ariffin, Mohd Farhan; Mohd Fadzil, Ahmad Zakwan (Online Journal of Research in Islamic Studies, 2025)
The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V), classifies pedophilia as a mental disorder. Despite this, numerous cases are reported daily, with many others going unreported due to the stigma and taboo surrounding the issue. This paper aims to identify patterns in previous research on pedophilia by utilizing the Systematic Literature Review (SLR) method. This approach involves systematically framing, identifying, evaluating, and analyzing prior studies on preventive interventions for pedophilia through a structured process. The findings highlight several key issues for discussion, including legal frameworks, internet usage, types of pedophilic offenders, and the distribution of child pornography. Contributing factors to pedophilia are identified as psychological, social, educational, socioeconomic, and cultural influences. The results also emphasize existing efforts in preventive interventions, such as legal enforcement, educational programs, and the integration of Islamic cognitive and psychospiritual values. This study underscores that pedophilia presents a significant and urgent threat that requires focused attention. While various studies have explored its contributing factors and preventive measures, there remains a critical need for comprehensive interventions that actively engage both guardians and children. Therefore, the development of a holistic model centered on prevention and child protection is crucial. Such a model would not only address this crime effectively but also contribute to achieving the Sustainable Development Goals (SDGs), particularly in promoting a healthy and harmonious environment at the national level.